2001
DOI: 10.1002/mc.1051
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of loss of heterozygosity caused by hemizygous deletions in renal cell carcinoma using a subtraction library

Abstract: Several new loci were identified by a comprehensive analysis of loss of heterozygosity (LOH) using a subtraction library between matched normal and renal cell carcinoma (RCC) tissues. A total of 187 clones from the library, with a complexity of 1x10(4), were mapped, and 44 clusters of the mapped loci were subjected to LOH analysis using microsatellite markers. A total of 27 loci, which exhibited frequencies of LOH of at least 10% among 44 tumors, mostly clear-cell RCC, included several loci that were reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…We previously reported 27 potential tumor-related loci using a library obtained by subtraction of tumor tissue DNA from normal tissue DNA of the same patient (14). By extensive analysis of LOH in RCC tissues using microsatellite markers, one of the loci on chromosome 9 was found to show a relatively high incidence of LOH (25%, 5 of 20 cases) (14). The minimum overlapping region of LOH at this 9p24 locus was further narrowed down to a region 165 kb in size (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported 27 potential tumor-related loci using a library obtained by subtraction of tumor tissue DNA from normal tissue DNA of the same patient (14). By extensive analysis of LOH in RCC tissues using microsatellite markers, one of the loci on chromosome 9 was found to show a relatively high incidence of LOH (25%, 5 of 20 cases) (14). The minimum overlapping region of LOH at this 9p24 locus was further narrowed down to a region 165 kb in size (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LOH Analysis-LOH analysis using GeneScan Version 3.1 (Applied Biosystems, Inc.) was performed as described previously (14). For LOH analysis of patient R6, genomic DNA was extracted from primary culture cells derived from normal and tumor tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In renal cancer cells, it has been reported that Rac is a key regulator of cytoskeleton organization during hypoxia, and modulation of the Rac-actin pathway is essential for renal cell carcinoma development [Engers et al, 2001]. Indeed, it has been hypothesized that a candidate tumor suppressor gene in ccRCC might function by controlling the formation of the cytoskeleton through polymerization of actin [Hatano et al, 2001;Sarkar et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study based on more than 5,000 RCC cases revealed two loci, 2p21 and 11q13.3, to be associated with RCC susceptibility (Purdue et al, 2011). Although the authors claimed these sites to be previously unidentified, both of the loci were actually identified in 2001 (Hatano et al, 2001; Table 1). While the association is statistically significant, the frequencies among RCC cases are not very high (less than 20%), and therefore, it is doubtful that these sites alone can be used for diagnosis.…”
Section: Exploration Of New Genetic Markersmentioning
confidence: 99%